Prefeasibility Analysis of Off-Grid HRES for Telecom Station - Kumari, Sweta; Sinha, U. K. (International Journal of Engineering and Technology, 2026)
As of now, utility has started to consider the green power innovation for having a more beneficial condition. The green power technolo-gies lessen ignition of petroleum derivatives and the resultant co2 discharge that will be that the guideline explanation for a dangerous atmospheric warming. By boosting the use of the sustainable power source, the use of diesel generator for driving the base transceiver stations might be decreased or removed. This paper plans to research the financial, specialized and ecological execution of hybrid power systems for powering remote telecom base station. Simulations using HOMER software are performed to determine the Initial Capital, the Total net present cost, COE assist claiming the framework limit deficiency of the different supply choices. The simulation results recommend an appropriate hybrid system which might be the feasible solution for generation of electric power for remote telecom base station. A nearby examination, description and modelling of the system also are exhibited in this paper.